Trinidad and Tobago : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This Selected Issues paper reviews the performance and reform plans for public bodies (PBs) in Trinidad and Tobago. PBs represent a source of fiscal risk to the government through the generation of financial losses, with current and capital transfers from the central government to PBs amounting to 3.5 percent of GDP in FY2015/16. Inappropriate pricing policy and weak governance are the most prevalent sources of fiscal risk. PBs must improve public service delivery and become profitable. Key policies should center on incentives for performance, stronger corporate governance, and better public oversight. Steadfast restructuring of PBs with losses must be implemented either through restructuring those that are nonviable or liquidating them to ensure efficiency and improved resource allocation.